1997
DOI: 10.1080/03079459708419190
|View full text |Cite
|
Sign up to set email alerts
|

Fatty liver syndrome in captive bustards: Clinical, pathological and epidemiological findings

Abstract: SUMMARYClinical, pathological, and epidemiological findings are presented on fatty liver syndrome mainly in houbara bustards (Chlamydotis undulata macqueenii), but also in some other bustard species. Of 72 houbara bustards, 34 (47%) had fatty liver diagnosed post-mortem. Males and females were equally susceptible, and both adults and juvenile birds were affected. Bustards with fatty liver had significantly greater abdominal fat reserves than unaffected birds. Other predisposing factors included poor husbandry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Another challenge is the effective acquisition of clinical information in a format that can easily be captured by the computer for subsequent statistical evaluation. 33 Free-text-based computer records allow data to be entered in many different ways, 27 but text queries become difficult because of the use of abbreviations, lexical variants (i.e., hypertensive, hypertension), and synonyms. 15 Even for a relatively well-defined condition, such as atoxoplasmosis, this study found at least five different ways of recording it on the problem list.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another challenge is the effective acquisition of clinical information in a format that can easily be captured by the computer for subsequent statistical evaluation. 33 Free-text-based computer records allow data to be entered in many different ways, 27 but text queries become difficult because of the use of abbreviations, lexical variants (i.e., hypertensive, hypertension), and synonyms. 15 Even for a relatively well-defined condition, such as atoxoplasmosis, this study found at least five different ways of recording it on the problem list.…”
Section: Discussionmentioning
confidence: 99%
“…25,26,34 Review of epidemiologic studies of captive wildlife reveals historic surveys of disease, 9 data collected via questionnaires, 6 and studies investigating the prevalence and control and risk factors for disease. 11,17,23,27,35 There continues to be a demand for expansion of the scope, scale, quality, and timeliness of epidemiologic data from zoologic collections as the focus on zoologic collection management increases. 5 Suggestions and guidelines have been developed regarding specific data that are needed for epidemiologic studies and surveillance systems to determine disease prevalence, morbidity and mortality, common clinical signs, disease risk factors, adverse drug reactions, and anesthetic drug responses.…”
Section: Introductionmentioning
confidence: 99%